Persepsi dan Sikap Nelayan Sondong Tentang Larangan Menggunakan Alat Tangkap Sondong di Desa Muara Gading Mas Labuhan Maringgai - M. Hadziq Qulubi; Diah Apriliyana; Desy Sasri Untari (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2024)
In PERMEN KP No. 2 Year 2015 sondong fishing gear is part of a trawls catcher that is potentially damaging to the marine ecosystem. However, But in Muara Gading Mas Village, Sondong's fishing gear is still used by fishermen.The purpose of this study is to know the perception and attitude of fishermen in respect of the ban on the use of fishing devices sondong in Muara Gading Mas village as well as to know what follow-up the government is doing. The method used in this research is qualitative descriptive, with data sources as primary data and secondary data. Data collection is done with observations, interviews and documentation, which is then analyzed with data reduction, data presentation and conclusion drawing. As a result of research that shows fishermen's perception of the ban on the use of sondong and knowledge indicators show that the majority of fisherman (57.89%) are unaware of the prohibition, the dominant awareness indicator (55.26%) has not yet been aware of leaving the probes, and the indicator of compliance of most (57.8%) are not willing to switch to environmentally friendly probes. UPTD PP Labuhan Maringgai and Teladas with the support of the Department of Maritime Affairs undertakes socialization efforts, evaluation as well as follow-up to the enforcement of the ban on the use of Sondong capture equipment.